THE RELATIONSHIP OF NEUTROPHIL-TO-LYMPHOCYTE RATIO (NLR) WITH LOCALIZED AND NON-LOCALIZED TESTICULAR GERM CELL TUMORS - Seputra, Kurnia Penta; Nurhadi, Pradana; Husein, Rahmat (Indonesian Urological Association, 2025)
Objective: This study aim to reveal the relationship preoperative neutrophil-to-lymphocyte ratio (NLR) with testicular germ cell tumors (GCT). Material & Methods: A total of twenty-six patients diagnosed with TGCT from 2017 to 2022 in Saiful Anwar Hospital, Malang were included in this retrospective study. Patients were grouped as localized and non-localized. Hematological and biochemical blood measured the days before radical orchiectomy. Results: Eleven patients (42.3%) had seminomas and fifteen patients (57.7%) had non-seminomatous testicular cancer. Six patients (23.1%) had localized and twenty patients (76.9%) had non-localized testicular cancer. There was a statistically significant difference between mean NLR of the localized patients and non-localized patients (localized NLR: 1.7±0.84, non-localized: 3.65±0.97, p=0.000). The optimal cut-off value for localized and non-localized TGCT was 3.05 with sensitivity 83.33% and specificity 75%. That was statistically significant between cut-off value NLR with localized and non-localized TGCT (correlation coefficient 0.505, p=0.008). Conclusion: NLR appears to be a useful marker for TGCT. It is successful in predicting localized and non-localized disease in early preoperative period. Keywords: Neutrophil-to-lymphocyte ratio, testicular cancer, testicular germ cell tumors.